All the options have the "x" variable isolated on the left side, so to find the one that is equivalent to the given expression we will isolate the "x" variable. This is done by switching terms from one side to the other on the equation. The first step is to subtract both sides by "y". We have:
![\begin{gathered} 2x+y=3 \\ 2x+y-y=3-y \\ 2x=3-y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7pj78v468lnp6npb1tkvyaf9m0u14i7aii.png)
Then we need to divide both sides by 2.
![\begin{gathered} (2x)/(2)=(3-y)/(2) \\ x=(3-y)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9ay6wnuakjnkgw8b2athduds1y2lgekd1o.png)
The correct option is the last one.